2019
DOI: 10.3390/ma12203374
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Strengthening Mechanism of SiC/Al Composites Fabricated by a Liquid-Pressing Process and Heat Treatment

Abstract: Aluminum alloy (Al7075) composites reinforced with a high volume fraction of silicon carbide (SiC) were produced by a liquid-pressing process. The characterization of their microstructure showed that SiC particles corresponding to a volume fraction greater than 60% were uniformly distributed in the composite, and Mg2Si precipitates were present at the interface between the matrix and the reinforcement. A superior compressive strength (1130 MPa) was obtained by an effective load transfer to the hard ceramic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Though the tensile strength is lower than that in novel processes [ 10 , 30 , 31 , 32 ], the bending strength and compression strength were greatly improved. The discrepancy in compression and tensile strength revealed a conversion in which the plasticity composite showed a small part of brittleness features after the resin addition.…”
Section: Resultsmentioning
confidence: 99%
“…Though the tensile strength is lower than that in novel processes [ 10 , 30 , 31 , 32 ], the bending strength and compression strength were greatly improved. The discrepancy in compression and tensile strength revealed a conversion in which the plasticity composite showed a small part of brittleness features after the resin addition.…”
Section: Resultsmentioning
confidence: 99%
“…From the contour and 3D surface plots for variation of YS with varying wt.% of reinforcements at different heat treatment temperatures, it is clearly evident that the reinforcements and heat treatment increases the yield strength of the composites, attributed to Orowan strengthening facilitated by precipitation hardening. Shin et al [43] identified the microstructural evolution and strengthening mechanisms in Al/SiC composites en route the liquid pressing process, subsequently followed by the heat treatment process, which helps in increasing the strength due to solution heat treatment and artificial ageing, especially due to the formation of Mg 2 Si precipitates attributed to precipitation hardening. From the contour and 3D surface plots for variation of YS with varying wt.% of reinforcements at different heat treatment temperatures, it is clearly evident that the reinforcements and heat treatment increases the yield strength of the composites, attributed to Orowan strengthening facilitated by precipitation hardening.…”
Section:  Yield Strengthmentioning
confidence: 99%
“…Some of the strengthening mechanisms that can be operative in MMCs are Orowan strengthening, Hall petch strengthening, dislocation strengthening, load transfer strengthening, thermal mismatch strengthening, grain refinement and work hardening. [17][18][19][20][21][22][23] Composite materials are normally classified according to the matrix material. MMCs consist of a metallic matrix and a dispersed metallic or ceramic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, understanding the strengthening mechanisms and hence predicting the yield strength is important for fabricating high performance and quality MMC components. Some of the strengthening mechanisms that can be operative in MMCs are Orowan strengthening, Hall petch strengthening, dislocation strengthening, load transfer strengthening, thermal mismatch strengthening, grain refinement and work hardening 17‐23 …”
Section: Introductionmentioning
confidence: 99%